On exact solutions of the generalized Pochhammer-Chree equation - Yokus, Asif; Ali, Karmina K.; Yilmazer, Resat; Bulut, Hasan (Univ Tabriz, 2022)
In the current study, we consider the generalized Pochhammer-Chree equation with a term of order n. Based on the (1/G')-expansion method and with the aid of symbolic computation, we construct some distinct exact solutions for this nonlinear model. Various exact solutions are produced to the studied equation including singular solutions and periodic wave solutions. In addition, 2D, 3D, and contour plots are graphed for all obtaining solutions via choosing the suitable values for the involved parameters. All gained solutions verify the governing equation.
Keywords: The generalized Pochhammer-Chree equation; The (1 /G ')-expansion method; Exact wave solutions